9th ASME International Conference on Radioactive Waste Management and Environmental Remediation: Volumes 1, 2, and 3 2003
DOI: 10.1115/icem2003-4766
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Palladium During Spent Fuel Reprocessing

Abstract: The principal purpose of spent fuel reprocessing consists in the recovery of the uranium and plutonium and the separation of fission products so as to allow re-use of fissile and fertile isotopes and facilitate disposal of waste elements. Amongst the fission products present in spent nuclear fuel of Nuclear Power Plants (NPPs,) there are considerable quantities of platinum group metals (PGMs): ruthenium, rhodium and palladium. Given current predictions for nuclear power generation, it is predicted that the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Palladium isotopes are generated during nuclear reactions along with many other fission products. Both radio and stable isotopes can be found in spent nuclear fuel and high-level radioactive waste (HLW). , Among these isotopes, 107 Pd is the only long-lived nuclide (half-life: 6.5 × 10 6 y). Thus, the determination of the 107 Pd content in radioactive waste is considered crucial for safety evaluation in managing such wastes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Palladium isotopes are generated during nuclear reactions along with many other fission products. Both radio and stable isotopes can be found in spent nuclear fuel and high-level radioactive waste (HLW). , Among these isotopes, 107 Pd is the only long-lived nuclide (half-life: 6.5 × 10 6 y). Thus, the determination of the 107 Pd content in radioactive waste is considered crucial for safety evaluation in managing such wastes.…”
mentioning
confidence: 99%
“…Other than the low specific activity of 107 Pd, the instability of trace Pd ions in an aqueous solution may have some connection to the difficulties in detecting 107 Pd in radioactive wastes. Several reports showed that Pd is likely to form a precipitate that can be incorporated into insoluble residue in an HNO 3 matrix. ,, This makes it difficult to track the migration path of dissolved species in waste processing.…”
mentioning
confidence: 99%
See 1 more Smart Citation